Eco-Pedal Bicycle Prototype Design as An Alternative Multi-Information Display Energy Generator - Sefrani Isdarmayani Siregar; Syamsyarief Baqaruzi; Rachmad Hidayatullah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2021)
As technology grows, so does the consumption of energy, especially electricity. Today, electricity has become the most used energy worldwide and the demand keeps on increasing every year. According to PLN annual report the highest electricity consumption came from domestic sector which peak up to 97.832,28 GWh in 2018. Sadly, our current power supplies are not enough to fulfill those demands. It was the main reason to develop another form of cheaper, more efficient, and environmentally friendly power plants. This research aims to build a simple system which able to generate electricity for bicycle and to determine the voltage and the current it generates with certain speed which can be stored in portable batteries in order to meet the campus power demand. This design uses propulsion from the bicycle and using a 16.8 volt 6600 mAh Lithium-ion battery as its energy storage. The tests show that MID LCD may update and notify the changes of voltage, temperature, speed in every second. The average power released is 13 Watt with maximum output can reach 34 Watt. The test shows that the average voltage error is 0.79% while average temperature error is 1.28% and average speed error is 2.77%.